The influence of gender-based perceptions on females joining a bachelor of medicine, bachelor of surgery in Rwanda - Tsion Yohannes Waka; Deborah Umucyo; Arlene Nishimwe; Abigail J. Yoon; Kara L. Neil (BMC Medical Education)
Abstract Through progressive policies, Rwanda has made significant strides in promoting girls’ education and empowerment. However, female enrollment in Bachelor of Medicine and Bachelor of Surgery (MBBS) programs remains disproportionately low. This cross-sectional study investigates the influence of gender stereotypes and girls’ self-perceptions on female engagement in MBBS programs in Rwanda. The data analyzed for this study has been used and published in BMC Medical Education in a study with a different but clearly related focus, under the title “Gender-based support systems influencing female students to pursue a bachelor of medicine, bachelor of surgery (MBBS) in Rwanda” (Neil KL, BMC Med Educ 24:641,2024). While the previous analysis focused on the presence and gaps in gender-based support systems, the current research has a new focus on gender based self-perceptions influence in girls interest in pursuing medical school training. Conducted across 13 secondary schools and 3 universities offering MBBS degrees, the study engaged 8–12 students, parents/guardians, and teachers in each focus group discussion in a total of thirty-four focus group discussions and sixteen semi-structured interviews. Twenty-eight discussions took place at the secondary school level, and six were conducted at the MBBS level. Data analysis utilized inductive coding to identify recurring themes. The study identified three overarching themes: society’s role in shaping gendered expectations about domestic and professional roles, girls’ self-perceptions regarding their ability to pursue sciences and MBBS within these norms, and internalized stereotypes affecting girls’ career aspirations. Drawing on gender schema and social cognitive theory, the research underscores how societal expectations and stereotypes shape and constrain girls’ career choices. The findings highlight the necessity of dismantling gender-based perceptions that hinder girls’ participation in scientific disciplines, including MBBS.